Resource Letter RBAI-1: Research-Based Assessment Instruments in Physics and Astronomy - Madsen, A.; McKagan, S. B.; Sayre, Eleanor C. (My University, 2017)
This resource letter provides a guide to Research-Based Assessment Instruments (RBAIs) of physics and astronomy content. These are standardized assessments that were rigorously developed and revised using student ideas and interviews, expert input, and statistical analyses. RBAIs have had a major impact on physics and astronomy education reform by providing a universal and convincing measure of student understanding that instructors can use to assess and improve the effectiveness of their teaching. In this resource letter, we present an overview of all content RBAIs in physics and astronomy by topic, research validation, instructional level, format, and themes, to help faculty find the best assessment for their course. More details about each RBAI available in physics and astronomy are available at PhysPort: physport. org/assessments. (C) 2017 American Association of Physics Teachers.
Citation: Madsen, A., McKagan, S. B., & Sayre, E. C. (2017). Resource Letter RBAI-1: Research-Based Assessment Instruments in Physics and Astronomy. American Journal of Physics, 85(4), 245-264. doi:10.1119/1.4977416
Keywords: Classical Mechanics/Math Methods; Quantum-Mechanics; Rotational; Kinematics; Conceptual Survey; Introductory Physics